Dark traces of the past : psychoanalysis and historical thinking - Straub, Jürgen, 1958-; Rüsen, Jörn (Making sense of history, 2010)
The relationship between historical studies and psychoanalysis remains an open debate that is full of tension, in both a positive and negative sense. In particular the following question has not been answered satisfactorily: what distinguishes a psychoanalytical-oriented study of historical realities from a historical psychoanalysis?